2013
DOI: 10.3109/09638288.2012.754953
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality after stroke: patient counseling preferences

Abstract: Many stroke survivors experience sexual dysfunction and indicate a desire for additional information and counseling from healthcare providers. Preferences regarding the timing of such counseling vary, creating challenges for optimizing the delivery of this care. IMPLICATIONS FOR STROKE REHABILITATION: Sexual dysfunction is common after stroke, but is frequently not addressed by healthcare providers. Many stroke survivors experience sexual dysfunction and indicate a desire for additional information and counsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 33 publications
3
58
0
6
Order By: Relevance
“…This information does not have to be very extensive, but basic information on what to expect or what to do with the prosthesis for example, would have been welcomed by the majority of participants. As suggested in other studies, the current study confirmed that the timing of providing this kind of information is crucial [39,40]. In the beginning of the rehabilitation process, people are trying to recover from the amputation, and are learning to walk with the prosthesis.…”
Section: Discussionsupporting
confidence: 90%
“…This information does not have to be very extensive, but basic information on what to expect or what to do with the prosthesis for example, would have been welcomed by the majority of participants. As suggested in other studies, the current study confirmed that the timing of providing this kind of information is crucial [39,40]. In the beginning of the rehabilitation process, people are trying to recover from the amputation, and are learning to walk with the prosthesis.…”
Section: Discussionsupporting
confidence: 90%
“…890 Stroke survivors report a desire for more information about sexuality from healthcare providers, physicians in particular. 891 It is important for the patient and significant other to know that sex is not contraindicated after stroke. The most common sexual dysfunctions after stroke are decreased libido, erection and ejaculation disorders in men, lubrication and orgasm in women, and self-image and role changes for both men and women.…”
Section: Sexual Functionmentioning
confidence: 99%
“…There is a large body of evidence across cultures and stroke severities that patients after stroke want to learn and talk about sexual health, but are not receiving the information that they want from healthcare providers [1][2][3][4].…”
Section: Problemmentioning
confidence: 99%